TRANSCENDING ACADEMY: THE BEGINNINGS OF THE JOURNAL NEXUS (1978-1982) (Tzintzun, Revista de Estudios Históricos, 2022)
This article focuses on the background of the Mexican cultural magazine Nexosand on the first four years of its existence, in which the historian EnriqueFlorescano served as its director (1978-1982). Taking as a premise the fact thatmagazines are spaces with their own characteristics and dynamics and, at thesame time, spaces that condense, materialize and express certain historicalprocesses, this text moves on two levels. On the one hand, it studies the particulardevelopment of the magazine and the network of individuals that was formedaround it from multiple sources, giving a preponderant place to interviews withthe protagonists. On the other, the political, cultural and social context that madeits emergence possible and shaped some of its main features is analyzed.
Keywords: Nexos magazine; Enrique Florescano; cultural history